Character of meibomian gland dysfunction in patients with diabetic polyneuropathy with severe complications (Ukrainian Journal of Ophthalmology, 2026)
Background. Meibomian gland dysfunction (MGD) is a chronic, diffuse abnormality of the meibomian glands, commonly characterized by terminal duct obstruction and/or qualitative/quantitative changes in the glandular secretion. Diabetic polyneuropathy can be a cause of MGD.Purpose: To improve the efficacy of diagnosis of MGD in patients with severe complications of diabetic polyneuropathy.Materials and Methods: Standard ophthalmological examination, the Schirmer’s test before and 2 hours after eyelid compression, the Norn’s test, the OPI test, a compression test, an IVAD test, contact meibography with green filter were performed. Severe complications of diabetic polyneuropathy (N3 stage) were recorded in 25 patients (50 eyes). A control group consisted of 97 persons (194 eyes) without diabetes.Results and Discussion: The Schirmer’s test was 2.7 times reduced in patients with N3 stage (4.83 mm) in comparison with that in the control group (12.82) (p
Keywords: meibomian glands dysfunction; diabetic polyneuropathy; Schirmer’s test; contact meibography; meibomian gland secretions